Pseudomonad bacterial epiphyte studies in Colorado - Legard, D.E.; Schwartz, Howard F.; Garrett, K.A. (1986)
Results of the research on beans carried out by the Dept. of Plant Pathology and Weed Science of Colorado State U. (USA) are briefly summarized. Surveys in the spring of 1984 and 1985 found many wild beans infected with, and/or colonized by, populations of Pseudomonas syringae pv. phaseolicola and P. syringae pv. syringae. In an evaluation of bean seedlings in commercial fields no symptoms of Pseudomonas were detected. The effect of 2 spray programs (early and late) was evaluated in commercial bean plantings. The early and late preventive spray programs were equally effective in reducing epiphytic syringae-type pseudomonads. (CIAT)